2013
DOI: 10.3390/nu5083022
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium and Osteoporosis: Current State of Knowledge and Future Research Directions

Abstract: A tight control of magnesium homeostasis seems to be crucial for bone health. On the basis of experimental and epidemiological studies, both low and high magnesium have harmful effects on the bones. Magnesium deficiency contributes to osteoporosis directly by acting on crystal formation and on bone cells and indirectly by impacting on the secretion and the activity of parathyroid hormone and by promoting low grade inflammation. Less is known about the mechanisms responsible for the mineralization defects obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
312
2
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 407 publications
(369 citation statements)
references
References 59 publications
10
312
2
12
Order By: Relevance
“…17 In our study also serum Mg level is significantly lower (p<0.001) in postmenopausal women when compared to premenopausal women. Mg level also had a positive correlation with T score in both the groups which explains role of Magnesium in osteoporosis.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…17 In our study also serum Mg level is significantly lower (p<0.001) in postmenopausal women when compared to premenopausal women. Mg level also had a positive correlation with T score in both the groups which explains role of Magnesium in osteoporosis.…”
Section: Resultsmentioning
confidence: 58%
“…Approximately 50 per cent of it is present in our bones. Magnesium helps prevent osteopenia and osteoporosis in the following ways: 7,16,17 • Magnesium helps control hundreds of enzymatic reactions in cells that influence bone density.…”
Section: Resultsmentioning
confidence: 99%
“…Some authors claim that their levels rise after ovariectomy [17], others prove the opposite data [18]. A fall in estrogen levels increases the resorptive effect of parathyroid hormone (PTH), which would lead to hypercalcemia, hyperphosphatemia [17] and hypomagnesaemia [19,20]. However, a compensatory mechanism that reduces intestinal absorption and increases renal calcium excretion is triggered [21].…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis are induced experimentally through different methods (18)(19)(20) , one of main method to induce osteopetrosis is ovariectomy (21)(22)(23)(24)(25)(26) but it was found that rabbits constitutes a poor model for exclusively ovarian function deprivation osteoporosis. Failure in achieving significant reductions in bone mass of rabbit could be explained by presence of reflex ovulations or an ectopic production of sexual hormones (27) , so osteoporosis were induced in present study by using GCs.…”
Section: Discussionmentioning
confidence: 99%